BANKRUPTCY PREDICTION ANALYSIS USING THE ZMIJEWSKI MODEL (X-SCORE) AND THE ALTMAN MODEL (Z-SCORE) - Viciwati, Viciwati (Dinasti International Journal of Economics, Finance & Accounting, 2020)
This study aims to identify and analyze the accurate models of Financial Distress in retail companies listed on the Indonesian Stock Exchange in 2014-2018 using the Zmijewski (X-Score) and Altman (Z-Score) Model. The sample used is 70. This study uses secondary data from the 2014-2018 annual financial reports. This study tested the hypothesis using the normality test and the Kruskal Wallis test or the difference test using SPSS version 26. The results of this study indicate that the Zmijewski (X-Score) model is the model that has the highest accuracy rate in predicting bankruptcy with an accuracy rate of 90%.